Accounting and Financial Systems and Tools for Effective Leadership and Management - A Seetharaman; Nitin Patwa; Veena Jadhav; A. S. Saravanan (STIE Malangkucecwara, 2016)
Accounting and ﬁnancial systems and tools are widely used in performance measurement by leaders and managers. Although the deﬁnitions of leadership and management defer, the same tools are applied to manage organizations. The shift from the industrial age into today’s emerging information age has brought a great need for effective leadership and management. As performance is the epitome of a business enterprise, performance measurement is too important and too costly to get wrong. If the performance is not measurable, it is very difficult to manage operations of an enterprise. The last 2O years has witnessed a revolution of performance measurement ranging from financial ratios and budgetary control procedures by Dupont and General Motors, to organizational measurement systems, and next to the balance score card and Activity based budgeting, to name a few. An attempt is made to integrate practical and useful measurement (accounting, financial and non-accounting and non-financial) and management‘ systems and tools to harness their synergized benefits in strategies.